Mengembangkan Kecerdasan Finansial Dengan Matematika Keuangan - M. Yusuf; Muhamad Fajar Romadhan; Mohammad Lukman Toro; Achmad Maulana; Bardan Salsabil; Nurma Tambunan (International Forum of Researchers and Lecturers, 2023)
Financial intelligence is an individual's ability to understand, manage, and optimize the management of personal finances. Financial mathematics is becoming an important tool in developing financial intelligence. In this research using literature study method this method involves the search and collection of information from related literature sources. Through financial mathematics, one can calculate the future value of an investment, estimate the return on an investment, calculate annuity payments, understand the concept of time value of money, and analyze investment risk. The application of financial mathematics in financial intelligence provides an advantage in taking better financial decisions and managing finances effectively. By utilizing financial mathematics, one can improve their understanding of Finance, make effective financial planning, and take better financial decisions.